The willingness-to-accept/willingness-to-pay disparity in repeated markets: Loss aversion or 'bad-deal' aversion? - Andrea Isoni (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
Several experimental studies have reported that an otherwise robust regularity - the disparity between Willingness-To-Accept and Willingness-To-Pay - tends to be greatly reduced in repeated markets, posing a serious challenge to existing reference-dependent and reference-independent models alike. This paper offers a new account of the evidence, based on the assumptions that individuals are affected by good and bad deals relative to the expected transaction price (price sensitivity), with bad deals having a larger impact on their utility ('bad-deal'aversion). These features of preferences explain the existing evidence better than alternative approaches, including the most recent developments of loss aversion models.
Keywords: 330; WTA/WTP disparity; price sensitivity; bad-deal aversion; reference-dependence; loss aversion; Willingness to pay; Verlust; Angst; Theorie